Evaluation of apical leakage of root canals obturated with Nd:Yag laser softened gutta-percha, lateral and warm vertical condensation techniques using two types of endodontic sealers : an in vitro study - FARAJ, Bestoon; DAYEM, Raad; AL QAISI, Salam (International Arab Journal of Dentistry (IAJD), 2014)
An in vitro study was carried out to compare the apical leakage of root canals obturated with different techniques: Nd:YAG laser softened gutta-percha, cold lateral condensation and warm vertical condensation, and to evaluate the leakage of root fillings. Sixty human premolars (with single patent canal) were submitted to instrumentation by means of the step-back technique. The teeth were randomly divided into three experimental groups according to the obturation technique. The first group (n=20) was obturated by Nd:YAG laser softened gutta-percha, the second group (n=20) by cold lateral condensation and the third group (n=20) was obturated using the warm vertical condensation. Each group was divided into two equal subgroups depending on the type of sealer (AH 26® or Dorifill). Afterwards teeth received an impermeable coating on the external surfaces of the crown and root (except for the area nearby the apical foramen). After obturation, the access cavities were sealed and the teeth were immersed in aqueous 1% methylene blue dye for 7 days at 37ºC. After that, the teeth were longitudinally sectioned and the apical leakage was evaluated using a stereomicroscope. The warm vertical condensation presented the best apical sealing ability, followed by Nd:YAG laser and the lateral condensation technique. The statistical analysis of the apical leakage values showed no statistically significant differences between AH ®26 and Dorifill in leakage rate.